Effectiveness of Implementing Demonstration Methods in the Learning Process of Fiqh Subjects - Kartini, Kartini (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
Study on the effectiveness of implementing demonstration methods in the learning process of jurisprudence subjects. The problems discussed include the effectiveness of implementing the demonstration method at Madrasah Aliyah DDI Pattojo, Soppeng Regency. The aim of the author in choosing this discussion is because the theoretical learning process is widespread without being accompanied by practical ones, while the aim of learning, especially in the subject of jurisprudence, is to understand and practice. To examine this problem, this research is descriptive-qualitative research. The data collection procedure is through library research, namely by quoting available books related to the author's thesis, which are then quoted directly and indirectly, and field research. The author's data collection technique is conducting observations, interviews, documentation, and questionnaires with deductive, inductive, and comparative data analysis techniques. From the research process, it was found that the effectiveness of implementing the demonstration method in the learning process for Islamic jurisprudence subjects at the Madrasah Aliyah DDI Pattojo, Soppeng Regency was quite effective at the age of students who had already entered the phase of wanting to learn in a different atmosphere, not only in the classroom, but were constrained by the madrasa facilities, which is inadequate. However, basically, the effectiveness of implementing the demonstration method in the learning process for Islamic jurisprudence subjects at Madrasah Aliyah DDI Pattojo, Soppeng Regency, is quite good, but it is not evenly distributed due to the various obstacles above.